Analisis Tradisi dalam Pesan Dakwah Budaya Mandi Safar pada Masyarakat Muslim Seram Bagian Timur - Risqiatul Hasanah; Sitti Mutia Faradillah Tukwain (Alhadharah: Jurnal Ilmu Dakwah, 2021)
Safar bathing is a spiritual activity carried out in the month of Safar by some Muslims in several regions in Indonesia. One of the areas that is currently still executing it hereditary is the Seram district in the eastern part of the Maluku province. The Muslim community of the area believes that taking a Safar bath is part of the teachings of the Islamic religion that can resist reinforcements, avoid harm and be kept away from all diseases. Based on this, the researcher is interested in knowing how the message (maudlu ') of Islamic da'wah is found in the bathing tradition of the Muslim community in eastern Seram. This study uses descriptive qualitative methods, including interviews and observations. Interviews were conducted with religious leaders, community leaders, and the public who better understand the origins of taking a Safar bath. While observing, researchers directly observed the Muslim community of Eastern Seram. Based on the results of the study, it is known that the message of da'wah from bathing Safar includes aqidah, sharia and morals, where the message of da'wah in this tradition is not only building relationships with the Khaliq, but also relationships with others are maintained and maintained regardless of social status